Timetables of world literature - Kurian, George Thomas (New York : Facts on File, 2003)
Chronicles world literature from the Classical Age through the twentieth century, discussing literary developments and the relationship between literature and the political and social climate of each historical period
Includes bibliographical references (p. 299) and indexes
Keywords: Literature -- Chronology -- Juvenile literature; Literature -- Chronology